Effect of Hyaluronic acid injection in management of upper lip asymmetry after surgical correction of unilateral cleft lip ( Case report ) (Journal of Hama University, 2020)
Surgical repair of cleft lip, while correcting deformity and dysfunction, may leave residual cosmetic imperfections. The resultant asymmetry and low volume of the upper lip can be addressed surgically and via less invasive methods.We reported a case of a 27-year- old woman who suffered from unilateral cleft lip and has corrected surgically in childhood age. The treatment was by using injectable hyaluronic acid to correct the characteristic lip asymmetry and poor volume after surgical repair of a cleft lip.RESULTS We obtained a symmetric correction and aesthetically pleasing volume augmentation in the affected lip. These results lasted approximately 4 months.